Service Quality, Price Perception and Promotion Influence on Purchasing Decisions at Raxgacloth Screen Printed T-Shirt Convection - Priadi, Muhammad Fitroh Afrizal; Sumantri, Bambang Agus (Universitas Nusantara PGRI Kediri, 2024)
Research aim : The aim of this research is to identify the influence of service quality, price perception and promotion on purchasing decisions at the Raxgacloth screen-printed t-shirt convection, either partially or simultaneously. Design/Methode/Approach : The approach used in this research is a quantitative approach, causal research type, the sampling technique used was 40 respondents, and the data analysis technique used descriptive statistics, classical assumption tests, multiple linear. Regression, coefficient of determination, and hypothesis testing with SPSSv25 tools. Research Finding : The research results show that there is a significant influence between service quality, price perception and promotion simultaneously on purchasing decisions